Creation of Murine Experimental Abdominal Aortic Aneurysms with Elastase - Azuma, Junya (MyJove Corporation, 2009)
Transient intraluminal infusion of porcine pancreatic elastase into the infrarenal segment of the abdominal aorta is the most widely used animal model of abdominal aortic aneurysm (AAA) ever since it was first described in rats by Anidjar and colleagues.(1) The rationale for its development was based on the disrupted nature of elastin observed in AAAs. This rat model has been modified to produce AAAs in the infrarenal aortic region of mice.(2) The model has the ability to add broad insight into the pathobiology of AAA due to the emergence of numerous transgenic and gene knockout mice. Moreover, it is a viable platform to test potential therapeutic agents for AAA. In this video, we demonstrate the elastase infusion AAA procedure used in our laboratory. Mice are anesthetized using 2.5% isoflurane, and a laparotomy is performed under sterile conditions. The abdominal aortais isolated with the assistance of an operating stereomicroscope (Leica). After placing temporary ligatures around the proximal and distal aorta, an aortotomy is created at the bifurcation with the tip of a 30-gauge needle. A heat-tapered segment of PE-10 polyethylene tubing is introduced through the aortotomy and secured. The aortic lumen is subsequently perfused for 5-15 minutes at 100 mm Hg with saline containing type I porcine pancreatic elastase (4.5 U/mL; Sigma Chemical Co.). After removing the perfusion catheter, the aortotomy is repaired without constriction of the lumen.